Preparation and properties of PVDF based BaTiO3 containing nanocomposites - Mofokeng, Tladi Gideon (University of the Free State (Qwaqwa Campus), 2014)
The β-crystallization of PVDF was investigated in this study. Nanocomposites were prepared by melt mixing PVDF, and 80/20 w/w PVDF/PMMA blends, with non-activated and (5 and 10 min) mechanically activated BaTiO3 nanoparticles. The samples were then quenched in ice water followed by annealing at 80 °C for 24 hours. The sizes of the BaTiO3 particles were reduced through mechanical activation prior to mixing, and the activated BaTiO3 nanoparticles interacted better with the polymer matrix. The BaTiO3 nanoparticles were well dispersed in the polymer matrix, but also formed agglomerates. The β-phase was only detected in the blend and the blend nanocomposites. The non-activated BaTiO3 nanoparticles favoured the α-phase crystallization of PVDF/PMMA, while the mechanically activated nanoparticles induced the β-phase. The thermal stabilities of PVDF and the PVDF/PMMA blend decreased with the addition of BaTiO3 nanoparticles. At a fixed filler content, the storage modulus and dielectric constant increased with an increase in activation time. The crystallization and melting temperatures of the matrix were slightly affected by the introduction of activated BaTiO3 particles.
Keywords: Dissertation (M.Sc. (Chemistry))--University of the Free State (QwaQwa Campus), 2014; Titanium; Nanocomposites (Materials); Piezoelectricity; Dielectrics; Polymerization